Experimental measurements of wave-induced scour around a scaled gravity-based Oscillating Water Column Wave Energy Converter. (September 2022) - Lancaster, Orrin; Cossu, Remo; Wuppukondur, Ananth; Astorga Moar, Alejandro; Hunter, Scott; Baldock, Tom E.
Highlights: Scour patterns measured experimentally around a scaled Oscillating Water Column. Scour shown to undermine the structure, comparable with the tunnel erosion effect. Undermining scour leads to settlement of the gravity-based structure. Increasing the corner curvature shown to reduce scour depths by 23%. Comparison with field observations reveals similar scour patterns. Abstract: Experimental measurements of wave scour are reported for a 1:20 scaled model of an operating 200 kW Oscillating Water Column (OWC) Wave Energy Converter (WEC) in King Island, Tasmania, Australia. Test cases include different wave conditions (Keulegan-Carpenter (KC) number range of 0.45-1.02) and multiple geometric changes to the device, which are compared to scour measurements taken in the field around the King Island OWC WEC device. The measurements therefore provide the first ever comparison of field data with a scaled laboratory model of scour around an OWC WEC. Results highlight that scour forms at the back corners of the device before undermining the structure with depths up to 64 mm (scour depth to structure width ratio, S / B, of 0.094), although the magnitude of this scour is shown to be reduced by 23% by curving the back corners. Scour at the front of the device is highly sensitive to the configuration of the front chamber door, with very different scour scenarios depending on whether the chamber door is open, closed, or removed entirely. Comparison with field data shows that undermining scour at the back of the device is reproduced in both settings, and this leads to settlement of the structure in both the laboratory and field. This suggests that the physical modelling forms an accurate representation of a real-world site, and therefore demonstrates scour processes with applicability to OWC WECs and other gravity-based bluff body structures such as caissons or gravity-based foundations.